Depression and associated factors in type 2 diabetic patients: A community-based cross-sectional study from East Delhi - Kanika Singh; Anita Shankar Acharya; Sanjeev Kumar Rasania (Wolters Kluwer Medknow Publications, 2019)
Introduction: Diabetes is a chronic disease which has no cure and requires life-long management, frequent hospital visits, as well as monitoring of blood sugar levels, which can cause distress to the patient. Various risk factors have been identified that may influence the course of diabetes and its complication, of which depression has emerged as a significant factor. Diabetes mellitus doubles the likelihood of depression as compared to normal individuals. We conducted this study to find the prevalence of depression and its associated factors in diabetes mellitus patients in East Delhi. Material and Methods: A community-based cross-sectional study was conducted among 250 diabetics aged above 30 years in East Delhi in 2017. They were screened for depression using Physical Health Questionnaire 9. Sociodemographic details, diabetic profile, and behavioral factors were assessed. Data were collected and entered in SPSS software version 23. Multivariate analysis was done for associated factors. Results: Out of total 250 study patients who fulfilled the inclusion and exclusion criteria, 79 (31.6%) were males and 171 (68.4%) were females. Age, gender, marital status, type of family, diabetic profile, comorbidity, complications, blood pressure status, body mass index, physical activity, stress, and sleeping hours were the factors assessed for the association with depression. Conclusion: Diabetes is a chronic illness requiring a variety of self-management behaviors. To improve patients' diabetes self-management behaviors, health-care providers should cultivate patient-centered relationships. Screening of all diabetics for depression is of paramount importance.